Variable Renewable Energy Integration and Planning Study - World Bank (World Bank, Washington, DC, 2020)
This report is intended to answer the following critical questions for the future planning of the Pakistan electricity sector: What is the optimal energy mix over the next 10 to 20 years when considering economic, technical, and environmental factors? What are the implications for the basket cost of power, energy security, and greenhouse gas (GHG) emissions? Can the Pakistan electricity system handle much higher penetrations of variable renewable energy (VRE) such as solar and wind? If so, what are the implications for other generation sources such as hydropower and thermal plants already operating or planned? What capital investments, changes in operation, and planning decisions are needed to achieve an optimal energy mix, and when do they need to occur? The report presents the analysis and findings of a major study carried out over a period of 18 months involving all the key federal agencies involved in power system planning